THE EFFICACY OF THE CABLES OF 6–110 KV WITH XLPE INSULATION. Part 1 - M. A. Korotkevich; S. I. Podgaiskiy; A. V. Golomuzdov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
The assessment of the suitability of cables of 6–110 kV with XLPE insulation in comparison with cables of the same voltage but possessing paper-oil insulation has been fulfilled on the basis of the criterion of reduced costs. Thus, the comparison was undertaken between cables of various design and material of insulation: three-core paper insulated ones vs. three-core XLPE insulated ones; three-core paper-insulated ones vs. solid wires with XLPE insulation; single-core oil-filled cables of 110 kV with paper insulation vs. solid wires of 110 kV with XLPE insulation. The increase in long-term permissible current loads for cables with XLPE insulation because of the larger permissible temperature of heating in comparison with cables with paper-oil insulation complies with as would increase in the cross-sectional area of cable cores (equal to 0.61 from the original) and therefore reduces the cost of the cable by reducing the cost of manufacture of conductors. The reduced costs of the construction and operation of cable lines with XLPE insulation (accounting the increase in the cost of a cable 1.2 and 2 times as compared with the cost of a cable with three-core insulation), despite the decline in the cost of manufacture of conductors and the reduced annual operating costs (9 % and 17 % respectively of cable lines of voltage of up to 35 kV and 110 kV), occurred to be more than the reduced costs of the construction and operation of cable lines with paper insulation. Currently the cost of one meter of cable with XLPE insulation is less than the cost of cables of AAB, CASB, AASv types of a voltage of 10 kV with aluminium cores, that ensures their undeniable efficacy.